Admitting to bullying others or denying it: Differences in children’s psychosocial adjustment and implications for intervention - Garandeau, Claire F.; Turunen, Tiina; Trach, Jessica; Salmivalli, Christina (SAGE Publications, 2025)
This study examined whether, for bullying perpetrators, admitting to their behavior was associated with specific psychosocial characteristics, and whether it predicted decreases in bullying behavior and a higher responsiveness to a successful anti-bullying program after 9 months of implementation. It also investigated whether participation in an anti-bullying program deterred admitting to the behavior. At pretest, our sample included 5,908 children and early adolescents (Mage: 11.2 years) in 39 intervention and 38 control schools; among them, 1,304 were peer-identified bullying perpetrators (scoring higher or equal to 0.5 SD above the same-sex classroom mean). Regression analyses indicated that peer-identified bullying perpetrators who admitted to their behavior were more likely to suffer from internalizing problems and reported lower anti-bullying attitudes than those who did not admit to bullying others. There was no significant main effect of admitting to bullying on changes in peer-reported bullying 1 year later. However, in control schools only, those who admitted to bullying at pretest were more likely to continue bullying a year later than those who denied it. There was no evidence that participating in the anti-bullying program made it less likely for peer-identified bullying perpetrators to admit to their behavior.